Sex Differences in Vascular Reactivity in Mesenteric Arteries from a Mouse Model of Acute Intermittent Porphyria - Pulgar, Victor M. (Mol Genet Metab, 2019)
BACKGROUND AND AIMS: Acute intermittent porphyria (AIP) results from a partial deficiency of porphobilinogen deaminase (PBGD). Symptomatic AIP patients, most of whom are women, experience acute attacks characterized by severe abdominal pain and abrupt increases in blood pressure. Here, we characterized the reactivity of mesenteric arteries from male and female AIP mice with ~30% of normal PBGD activity and wild type C57BL/6 mice. METHODS: An acute porphyric attack was induced in AIP mice by treatment with phenobarbital. Vascular responses to K(+), phenylephrine (PE), acetylcholine (ACh), and hemin were determined (Wire Multi Myograph). RESULTS: Maximal contraction to PE was increased in arteries from male and female AIP mice (p<0.05) during an induced attack of acute porphyria. Female AIP arteries had increased sensitivity to PE (p<0.05) even after nitric oxide (NO) blockade with N(ω)-nitro-L-arginine methyl ester (L-NAME) (p<0.05). Maximal relaxation to ACh was similar in males and females with lower sensitivity in female AIP arteries (p<0.05). Hemin induced greater relaxation in AIP arteries in both males and females (p<0.05). SUMMARY/CONCLUSIONS: Sex differences in this AIP mouse model include a pro-contractile response in females. These alterations may contribute to the increased blood pressure during an acute attack and provide a novel mechanism of action whereby heme ameliorates the attacks.